Information content of IPO grading - Deb, Saikat Sovan; Marisetty, Vijaya B. (Journal of Banking & Finance, 2010)
In the year 2007, Indian capital market regulator-SEBI, introduced a unique certification mechanism for IPOs whereby all IPOs have to undergo mandatory quality grading by independent rating agencies. In this paper we argue that such objective, independent and exogenous certifying mechanism provides a better opportunity to test the well established certification hypothesis, especially in the context of emerging markets with institutional voids. Using a sample of 163 Indian IPOs we test the efficacy of IPO grading mechanism. We find, grading decreases IPO underpricing and positively influences demand of retail investors. Grading reduces secondary market risk and improves liquidity. However, grading does not affect long run performance of the IPOs. IPO grading successfully capture firm size, business group affiliation and firm’s quality of corporate governance. Our findings imply that, in emerging markets, regulator’s role to signal the quality of an IPO contributes towards the market welfare.